Kepemimpinan dan Performa Bermain Bola Tangan melalui Model Pendidikan Olahraga - Suherman Slamet; Yunyun Yudiana; Agus Mahendra; Amung Ma’mun (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2021)
The implementation of sports activities and learning is carried out to improve performance. The meaning of the values of sports, as the most important thing of positive sports development, has not been sufficiently revealed. The purpose of this study was to determine the differences in the development and mastery of the students through the implementation of sport education models containing leadership content and without leadership content. This study used a quasi-experimental control group pre-post test design involving 80 students as the samples through the purposive sampling technique. The samples were divided into two groups of students taking handball game courses. The results showed that there were two influential things, namely intentionally simulated student learning and general students learning without simulation. Thus, a ﬁnding of interest in the study was that after implementation of sport education models containing leadership content, performance enhancement in a 27% difference in the application of the simulated education model. Meanwhile, there was no difference in handball games performance, which means that both of them were affected. Furthermore, the development of leadership had a greater influence than the increase in handball games performance with a 22% difference. It might be because the students gained valuable values from the handball learning experience through the sports education model that is useful for learners and coaches and can be applied in sports clubs and, most importantly, in educational institutions.